Preventing Residential Burglary - Gillham, James R. author. aut Link
VII, 196 p.
Keywords: This book evaluates the newest efforts and initiative aimed at preventing burglary, discusses their merits and short- comings, and suggests how improvements might be incorporated in burglary prevention programs.